1999
DOI: 10.1046/j.1365-2346.1999.00418.x
|View full text |Cite
|
Sign up to set email alerts
|

Informed consent and patient participation in the medical encounter: a list of questions for an informed choice about the type of anaesthesia

Abstract: The present study was undertaken to evaluate the impact of a new procedure for eliciting informed consent by patients undergoing minor surgical procedures, in which the choice between general anaesthesia (GA) and regional anaesthesia (RA) was possible. In this prospective study, two randomly selected groups of patients were compared: study group (SG), 52 patients, received from the nurse before the preoperative interview, a list of seven questions, which they were invited to ask the anaesthetist; while the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Our primary outcome was a patient-centered evaluation of informed consent, which was developed based on previous studies [33][34][35][36][37][38] and the following three central informed consent elements: patient-reported understanding of the (1) reasons for and (2) risks of the procedure and (3) having had all questions answered. Specifically, we asked participants the following questions: (1) How well do you understand the reasons you need to have the procedure/surgery?…”
Section: Study Outcomesmentioning
confidence: 99%
“…Our primary outcome was a patient-centered evaluation of informed consent, which was developed based on previous studies [33][34][35][36][37][38] and the following three central informed consent elements: patient-reported understanding of the (1) reasons for and (2) risks of the procedure and (3) having had all questions answered. Specifically, we asked participants the following questions: (1) How well do you understand the reasons you need to have the procedure/surgery?…”
Section: Study Outcomesmentioning
confidence: 99%
“…Patients are typically given the QPL before their consultation to read through and determine which questions they would like answers to. Versions of the QPL have been utilized in a number of healthcare contexts including cancer,8 diabetes,13 coronary disease,14 geriatric medicine,15 general practice,16 gynecological and dermatological problems,17 surgical patients,18 and parents of children with neurological problems 19…”
mentioning
confidence: 99%
“…Use of the QPL in noncancer settings have shown variable results. For example, the QPL had no or little effect on the number of questions asked by diabetic patients34 and on self‐reported patient involvement by patients with coronary artery disease (CAD)34 and geriatric patients in primary care15, 16; however, a QPL to help patients about to undergo surgery in making an informed choice between general and regional anesthesia was found to significantly increase question‐asking in the consultation 18. It has been suggested that lack of effects in the former studies were due to the use of a general QPL containing questions that were not directly relevant to patients, and that disease‐specific interventions may have more success in improving patient involvement.…”
mentioning
confidence: 99%
“…Different versions of the prompt sheet have been developed in diverse fields of medicine, including general medicine, 17 geriatric medicine, 18 gynecological and dermatological conditions, 19 surgery, 20 diabetes, 21 and cancer. 22 There is, however, paucity of data on its use in the palliative care setting.…”
Section: Discussionmentioning
confidence: 99%